Wetting on fabrics - Liu, Ruili (Nanyang Technological University, 2022)
Textile-liquid interactions have been a focus of research in the textile industry for many years. How water interacts and behaves on textiles can differ greatly depending on many factors and parameters of the textile. In this project, how thread width and pore areas of textiles could affect the wetting behaviour of the textile is observed and analyzed.